The Optimal Dose of Intraoperative Dexmedetomidine for Antiemetic Effects of Post-operative Nausea and Vomiting in Patients Undergoing Elective Thoracic Surgery: A Retrospective Cohort Study - Li, Bing; Zhao, Ying; Liu, Xinmin; Liu, Yao; Zhang, Jiaqiang; Zhang, Wei (Frontiers in Medicine, 2022)
Abstract Background: Dexmedetomidine (DEX) administration decreases Postoperative nausea and vomiting (PONV), but it is a lack of large-scale retrospective cohort study and is unclear whether there is a dose-relationship and optimal dose for antiemetic effects between DEX and PONV. We performed a large-scale retrospective cohort study to explore the optimal dose of intraoperative DEX for antiemetic effects of PONV. Methods: A total of 5,310 patients aged ≥18 who underwent elective thoracic surgery from January 2016 to March 2020 under total intravenous anesthesia (TIVA) or combined intravenous and inhalation anesthesia in Henan Provincial People’s Hospital. Patients were divided into two groups, those who received DEX intraoperatively and those who did not receive DEX. Patients who received DEX after surgery were excluded. Our primary outcomes were the association, the dose-response relationship, and the optimal dose for antiemetic effects between intraoperative DEX and PONV. Results: Among the 3,878 patients enrolled, 2,553 patients received DEX and 1,325 patients did not receive DEX. The incidence of PONV in patients who received DEX was 21.3%, and the incidence of PONV in patients who did not receive DEX was 46.5% (P = .001). After the matched-pairs cohort consisted of 1,325 patients, the incidence of PONV in patients who received DEX was 23.6%, and the incidence of PONV in patients who did not receive DEX was 46.5% (P = .001). We analyzed three different models after propensity matching to validate the stability of the prediction model between intraoperative DEX and PONV. A dose-response relationship between intraoperative DEX and PONV was observed. The optimal dose range of intraoperative DEX for antiemetic effects of PONV is 50-100 µg in elective thoracic surgery. Conclusions: Intraoperative DEX was associated with a decreased incidence of PONV in the large-scale retrospective cohort study. A dose-response relationship between intraoperative DEX and PONV was observed. The optimal dose range of intraoperative DEX for antiemetic effects of PONV is 50-100 µg in elective thoracic surgery.